2013
DOI: 10.1016/j.electacta.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic corrosion between zinc and carbon steel investigated by local electrochemical impedance spectroscopy

Abstract: Nadine Pébère, et al.. Galvanic corrosion between zinc and carbon steel investigated by local electrochemical impedance spectroscopy. Electrochimica Acta, Elsevier, 2013Elsevier, , 88, pp.6-14. <10.1016Elsevier, /j.electacta.2012 b s t r a c tThe study of galvanic coupling between two metals is still a relevant topic, particularly in aerospace and automotive industries. The development of local electrochemical techniques leads to a better understanding of the phenomena occurring at the interfacial zone. Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 36 publications
(65 reference statements)
1
27
0
1
Order By: Relevance
“…The local impedance spectra measured over each of the three electrodes show in some cases an inductive loop at the high frequencies, Figure 5. This loop was observed clearly on the zinc electrode and also on the remote cathode, but not in the inner iron electrode, possibly because of a smaller geometrical distortion of the ionic flow [29]. The high and medium frequency portion of the spectrum is resistive, whereas at frequencies below ~100 Hz a constant-phase-element slope is observed, which corresponds to 10 -4 Fcm -2 s n-1 (with n=0.85) for both Fe1 and Fe2 and 10 -3 Fcm -2 s n-1 (with n=0.89) on zinc.…”
Section: Local Electrochemical Impedance Spectroscopy Leismentioning
confidence: 92%
“…The local impedance spectra measured over each of the three electrodes show in some cases an inductive loop at the high frequencies, Figure 5. This loop was observed clearly on the zinc electrode and also on the remote cathode, but not in the inner iron electrode, possibly because of a smaller geometrical distortion of the ionic flow [29]. The high and medium frequency portion of the spectrum is resistive, whereas at frequencies below ~100 Hz a constant-phase-element slope is observed, which corresponds to 10 -4 Fcm -2 s n-1 (with n=0.85) for both Fe1 and Fe2 and 10 -3 Fcm -2 s n-1 (with n=0.89) on zinc.…”
Section: Local Electrochemical Impedance Spectroscopy Leismentioning
confidence: 92%
“…Yin et al 5 studied galvanic corrosion behaviour of SM80SS and Ni-based alloy G3 at 30, 60 and 90 C under various ratios of area sizes conditions; they found that the galvanic current is proportional to the temperature and anode area ratio, and with increased anode area ratio, pits gradually deepen. Mouanga et al 6 studied galvanic corrosion behaviour by in situ electrochemical impedance spectroscopy for zinc and carbon steel, Lacroix et al 7 performed a research on galvanic corrosion behaviour between aluminum and magnesium, as well as Jorcin et al 8 studied the galvanic corrosion between copper and aluminium; the potential and current distributions on the surface of the model couple were obtained using Laplace equation through a finite element method algorithm; a good agreement was found between experimental and theoretical results. Various factors, which include anode area ratio, temperature, delivery of dissolved oxygen, as well as different kinds of surface passive film and material potential difference between dissimilar materials, affect galvanic corrosion.…”
Section: Introductionmentioning
confidence: 68%
“…[64][65][66] A possible cause could be the adsorption or desorption of activating or blocking species with increasing overpotential of each process. Two situations can be considered: (i) If the anodic adsorption (therefore cathodic desorption) of a blocking species occurs the inductive loop appears due to the dominant effect in the cathodic process; or (ii) if the anodic desorption (therefore cathodic adsorption) of a blocking species for the reactions (OIH layer) occurs then the observed inductive loop results as the dominant effect in the anodic component.…”
Section: Resultsmentioning
confidence: 99%